Drosophila hedgehog signaling range and robustness depend on direct and sustained heparan sulfate interactions - Manikowski, Dominique; Steffes, Georg; Froese, Jurij; Exner, Sebastian; Ehring, Kristina; Gude, Fabian; Di Iorio, Daniele; Wegner, Seraphine V.; Grobe, Kay (Frontiers in Molecular Biosciences, 2023)
Morphogens determine cellular differentiation in many developing tissues in a concentration dependent manner. As a central model for gradient formation during animal development, Hedgehog (Hh) morphogens spread away from their source to direct growth and pattern formation in the Drosophila wing disc. Although heparan sulfate (HS) expression in the disc is essential for this process, it is not known whether HS regulates Hh signaling and spread in a direct or in an indirect manner. To answer this question, we systematically screened two composite Hh binding areas for HS in vitro and expressed mutated proteins in the Drosophila wing disc. We found that selectively impaired HS binding of the second site reduced Hh signaling close to the source and caused striking wing mispatterning phenotypes more distant from the source. These observations suggest that HS constrains Hh to the wing disc epithelium in a direct manner, and that interfering with this constriction converts Hh into freely diffusing forms with altered signaling ranges and impaired gradient robustness.